The turning point science, society, and the rising culture - Capra, Fritjof (Flamingo, an imprint of HarperCollinsPublishers, 1983)
"We are trying to apply the concepts of an outdated world view--the mechanistic world view of Cartesian-Newtonian science--to a reality that can no longer be understood in terms of these concepts... To describe this world appropriately, we need an ecological perspective that the Cartesian world view does not offer." (Preface 15, 16)